2018
DOI: 10.1136/bcr-2018-224340
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of intractable visual hallucinations with 5-HT2Aantagonist ketanserin

Abstract: Hallucinations, visual, auditory or in another sensory modality, often respond well to treatment in patients with schizophrenia. Some, however, do not and can be very chronic and debilitating. We present a patient with schizophrenia with intractable hallucinations despite state of the art care, including high-dose clozapine and transcranial magnetic stimulation. Based on the possible role of the 5-HT receptor in hallucinations, we treated her with the antihypertensive drug ketanserin, a 5-HT receptor antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…More familiar to those in the psychedelic field, ketanserin, which readily blocks the effects of classic psychedelics (Preller et al, 2018), is not approved for the treatment of schizophrenia. However, in a case study of a patient with rare, childhood-onset, treatment-resistant schizophrenia, ketanserin did show a reduction in visual hallucinations, but did not improve auditory hallucinations or delusions while the patient remained on olanzapine, an atypical antipsychotic (Sommer et al, 2018).…”
Section: B Schizophrenia: Antagonist and Agonism At 5-ht2arsmentioning
confidence: 92%
“…More familiar to those in the psychedelic field, ketanserin, which readily blocks the effects of classic psychedelics (Preller et al, 2018), is not approved for the treatment of schizophrenia. However, in a case study of a patient with rare, childhood-onset, treatment-resistant schizophrenia, ketanserin did show a reduction in visual hallucinations, but did not improve auditory hallucinations or delusions while the patient remained on olanzapine, an atypical antipsychotic (Sommer et al, 2018).…”
Section: B Schizophrenia: Antagonist and Agonism At 5-ht2arsmentioning
confidence: 92%
“…Administration of the 5‐HT 2A antagonist ketanserin has been shown to block Psi and LSD‐induced psychoactive effects (Vollenweider et al, 1998; Kometer et al, 2013; Preller, Burt, et al, 2018). A recent study showed for the first time that ketanserin significantly reduced chronic, intractable visual hallucniation but not auditory hallucination in schizophrenia, suggesting a possible role of the 5‐HT 2A in the pathophysiology of visual hallucinations (Sommer et al, 2018). Further evidence also points toward a modulatory influence of the 5‐HT 1A receptor in mediating the psychoactive effects of Psi (Carter et al, 2005; Pokorny et al, 2016).…”
Section: Serotonergic Psychedelics and Social Adaptationmentioning
confidence: 99%
“…This category of patients could constitute a good candidate for type B schizophrenia (Howes and Kapur, 2014). Some recent case studies support this claim (Nasrallah et al, 2019;Sommer et al, 2018).…”
Section: Discussionmentioning
confidence: 82%